2022
DOI: 10.1111/bjd.21773
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, dermoscopic and histopathological findings in localized human monkeypox: a case from northern Italy

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 9 publications
5
48
0
2
Order By: Relevance
“…After the removal of duplicates (n = 738), 553 articles were screened by the reviewers. After filtering the titles and reading the abstracts, 74 articles were selected for full-text reading, and 28 were considered eligible for inclusion in this systematic review [ 7 , 8 , 22 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the removal of duplicates (n = 738), 553 articles were screened by the reviewers. After filtering the titles and reading the abstracts, 74 articles were selected for full-text reading, and 28 were considered eligible for inclusion in this systematic review [ 7 , 8 , 22 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the articles included in this review are summarized in Table 2 . Our review included 28 studies that were published between 1 January and 18 August 2022 [ 7 , 8 , 22 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. The studies (n = 28) reported case reports of sexually transmitted monkeypox with a detailed description of the number of cases, clinical manifestations, history of sexually transmitted diseases, method of diagnosis, location and course of skin lesions, and treatment ( Table 2 and Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, monkeypox disease in humans has been reported in more than 86 developed countries, with Europe being one of the most frequently affected areas [ 6 ]. Most cases of this outbreak, technically a pandemic, have been reported in men who have sex with other men (gay and bisexual population) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Spain is one of the countries with the highest number of reported cases in the world, and the Canary Islands, in particular, are one of the regions with the highest proportion of cases per number of inhabitants [ 16 ].…”
Section: Introductionmentioning
confidence: 99%